Challenged and satisfied: The role of organisational ownership and employee involvement - Tian, Amy; Gamble, J. (Routledge, 2016)
This study aims to offer a more fine-grained approach to our understanding of the relationship between job stress and job satisfaction. Building on organizational theory and Karasek’s (1979) Job Demand-Control model, we investigated an important institutional characteristic - organisational ownership - as an additional moderator to influence the interactive effects of job demands and control upon job satisfaction. Using data collected from 1,838 retail sector employees in China, we found that this three-way interaction was strongest for employees working in foreign-invested firms, who experienced higher employee involvement at work and perceived a high level of challenge-related stress. The relationship was weakest for employees in state-owned enterprises who reported low levels of both employee involvement and challenge-related stress. Our study constitutes an early attempt to assess the impact of institutional characteristics such as ownership on aspects of human resources management, and highlights the need for further research to recognize the importance of such characteristics as contextual factors that influence the effect of organisational practices and the work environment upon individual work-related outcomes. The paper’s concluding sections elaborate on the contributions our research makes both to theory as well as to the practicalities faced by human resource managers in contexts such as China.